THE STUDENTS' PERCEPTION ON ONLINE LEARNING DURING THE PANDEMIC COVID-19: THE CASE OF ENGLISH STUDENTS OF UIN SULTHAN THAHA SAIFUDDIN JAMBI - Zarmida, Riri; Saputra, Fauzan (Langue (Journal of Language and Education), 2023)
The objectives of the research to find out the students’ perception on online learning during the covid-19 at the Fifth Semester of English Education Department in UIN Sulthan Thaha Saifuddin Jambi in the year 2021/2022. The researcher used qualitative research as design method because it was comparable to collect the data from students’ perception, and gave interview to collecting the data. The data was collected from the fifth semester which have been learned using online learning. The sample were 3 students selected by purposive sampling. The research found that the majority of students had a positive perception of online learning based on the results of their interviews. They improved their learning through online learning and found a new understanding of the new media used by the lecturer in media online learning. On the other hand, some students gave perception that online learning has obstacles affected by a poor network, the quality of the student's mobile phone, and the capacity of the online learning application.